Potential of Soursop Leaf Extract Scrub as Antimicrobial - Jirna, Nyoman; Sudarmanto, Gede; Purna, Nyoman; Mastra, Nyoman; Suyasa, Nyoman Gede; Sundari, Cok Dewi Widhya Hana; Arjani, Ida Ayu Made Sri; Desi, Gusti Agung Ayu Satwikha (jitek, 2023)
Treatment of infectious diseases caused by bacteria has been carried out using antibiotics. However, the problem is resistance and even multi-resistance in bacteria. Preventive efforts are needed to anticipate, one of which is using soursop leaf extract scrub herbal products which contain gamma oryzanol compounds, flavonoids, phenols, and tannins as antimicrobials. This research is a pure experiment with one group pretest-posttest control design and positive and negative controls. The study aims to analyse the effectiveness of soursop leaf extract scrub products as antimicrobials on the skin of the respondents' arms before and after treatment. Antimicrobial counting uses the total plate count (TPC) method, with 118 respondents in-vivo, where the scrub is applied to the respondent's arm, measuring 10cm x 10cm for 10 minutes. The results of the data normality test with the Kolmogorov-Smirnov test obtained non-normally distributed data. The trial continued with a non-parametric test in the Wilcoxon test to get a significance value of 0.000 <0.05, which means that the soursop leaf extract scrub effectively reduces total bacteria count. The research may be helpful for the community in efforts to prevent skin infections caused by bacteria, and researchers need to conduct antibacterial tests for scrubs without soursop leaf extract as a comparison and conduct further tests such as safety tests, expiration periods and aesthetic tests on soursop leaf extract scrub products.